A Guided Template for PROPOSAL WRITING in Social Science Discipline - Khairunesa Isa; Sarala Thulasi Palpanadan (Penerbit UTHM, 2022)
This book, with the title A Guided Template for Proposal Writing in Social Science Discipline, is a step-by-step guide to help students with proposal writing to get through their proposal defence. Generally, it contains the fundamental elements and nature of research which is important in proposal writing. This first edition will guide students to write proposals starting with a literature review through Chapters One, Two, and Three. Relevant explanations with examples are provided to help students understand the topics discussed.